Speaking Anxiety Experienced by Junior High School Students and Their Strategies to Overcome the Anxiety - Sari, Tiara Widya (RETAIN : Journal of Research in English Language Teaching, 2023)
Speaking skill is considered as the most important skill because being able to speak fluently in English is one of the objective points in English learning. Although English as a global lingua franca is very important for students to master, speaking anxiety comes in a way as one major obstacle faced by students. This study uses a descriptive qualitative design to answer the research questions. The research subjects were four grade 7th junior high school students who experienced English speaking anxiety and had strategies to overcome their speaking anxiety. Research subjects were selected selectively using a closed questionnaire from all students in 7J class from one of the state junior high school in Surabaya. The instrument used in this research was interview. The findings show that there are three types of anxiety faced by students, namely apprehension of communication, test anxiety, and fear of negative or bad evaluation. The strategy used by students to overcome their speaking anxiety is the Social-Affective Strategy which consists of questioning, cooperating, self-talk, and self-reinforcement. Thus it can be concluded that the anxiety experienced by grade 7 junior high school students was most likely to occur during conversations, oral exams, or during class presentations. Each student has different strategies for dealing with their English speaking anxiety.